Gower handbook of library and information management - Prytherch Ray (Aldershot Gower, 1998)
The book begins with Part I analyzing the context and trends of the information world. In Part II, Strategy and Planning, the information environment is explored in more detail, with Chapters 3 and 4 presenting the main issues and principles of financial
Keywords: Great Britain; Information services-management; Library administration